The effect of male body mass index (BMI) on COVID- 19 disease infection - vahid seyedazizi (Sport Sciences and Health Research)
Background: Since the outbreak of COVID-19 virus and the rise in concerns, researchers have been investigating risk factors of this disease. One of the factors affecting the hospitalization of influenza patients is high BMI. Due to the relation between COVID-19 disease and influenza.Aim: the purpose of this study was to investigate the effect of BMI on the infection and severity of COVID-19 patients.Materials and Methods: BMI of 126 men was calculated and three groups of "appropriate weight", "overweight" and "obese" were identified. Then, the prevalence and severity of their disease were recorded. For data analysis, chi2 test was used in SPSS 26 software at a significance level of P= 0.05.Results: Prevalence of COVID-19 infection in the group with “appropriate weight”, ”overweight” and “fat” were 56%, 61% and 58%, respectively. Mild infection was reported in the three groups, 27%, 27% and 26%, respectively; Moderate infection was 22%, 26% and 26%, respectively; and severe infection was 7%, 8% and 5%, respectively. Therefore, there was no significant difference between their infection and the severity of infection in groups (P˃.05).Conclusion: Obesity has negative effect on the body's immune response and lung function. The hospitalization rate for influenza is higher in this group. But in infection of COVID-19 and severity of this disease, no significant difference was observed between men with different BMI. However, due to the relation between obesity, cardiovascular disease, diabetes, and the vulnerability of these patients to the COVID-19 virus, serious attention is necessary to prevent these individuals from COVID-19.